Seed treatment for improving quality of hybrid seeds of rice (Asian Journal of Medical and Biological Research, 2016)
Seeds of 15 hybrid rice varieties viz. Durber, Agomoni, Meghna, Hybrid super, Moyna, Tia, Gold, Aloron, Jagoron, Suborno, Safollo, Hira-1, Hira-2, Hira-4 and Hira-6 were collected from five different seed producing companies of Bangladesh. BAU-Biofungicide (3%), extracts of Garlic (1:1), Allamanda leaf (1:1) Bavistin (0.3%), Thiovit ( 0.3%) and Provax (0.3%) were used for treating seeds to improve quality of hybrid seeds of rice. The moisture content of seed samples ranged 12.20% to 14.37%, where highest moisture content was found in variety Meghna and lowest in variety Moyna. 1000-seed weight of seed samples ranged from 20.00 to 26.00g, where highest weight was recorded in Hira-4 and lowest was recorded both in Aloron and Hira-1. Seed health test revealed 11 different seed borne fungi viz. Bipolaris oryzae (0.0 to 25.5%), Fusarium moniliforme (0.00 to 3.0%), Fusarium oxysporum (0.0 to 18.0%), Aspergillus flavus (0.00 to 11.0%), Aspergillus niger (0.00 to 5.0%), Aspergillus candidus (0.00 to 15.0%), Penicillium spp. (0.0 to 7.0%) , Alternaria padwickii (0.0 to 1%), Alternaria tenuis (0.0 to 11.0%), Curvularia lunata (0.0 to 40.0%) and Nigrospora oryzae (0.0 to 4.0%) . Germination test resulted normal seedlings from 26.00 to 97.00%, where highest was recorded in variety Jagoron that treated with BAU-Biofungicide resulting highest increase in number of normal seedlings by 239.28% over untreated control. BAU-Biofungicide significantly decreased (upto 90.00%) formation of abnormal seedlings over untreated control. Moreover, BAU-Biofungicide increased up to 713.78% Vigor index over untreated control.Asian J. Med. Biol. Res. December 2015, 1(3): 406-415